MANAGEMENT OF PLANT PRODUCTION (NARCISSUS L.) THROUGH THE APPLICATION OF NON-STANDARD GROWING METHODS IN ORDER TO INCREASE THE FINANCIAL VALUE OF PRODUCTION - Bakmaz, Ognjen; Miloš Dragosavac; Jestrović, Vladimir; Radaković, Milan; Tatjana Davidov; Bjelica, Biljana; Brakus, Aleksandra; Popović, Dragana (Economics of Agriculture, 2023)
Geophytes are plants of high biological diversity that depends to a great extent on the growing process. Based on what is stated, any new method of production of Narcissus L. has a decisive effect on its production. The aim of the study is to determine if it is possible to achieve better economic-agricultural results with a new method/form of plant growing (Narcissus L., Amaryllidaceae). Under the conditions of the Pannonian environment the production of two methods/forms of growing is compared. By measuring physical plant parameters (p=.00) the results show that the production is better using the standard method of growing. The realized value on the market is higher for the plants grown using the standard method of production (p<.05). The contribution of the author of the study is to indicate a new way of growing, which leads to a higher total value of production.